Incomplete reporting of enhanced recovery elements and its impact on achieving quality improvement. Issue 13 (14th September 2015) - Day, R. W.; Fielder, S.; Calhoun, J.; Kehlet, H.; Gottumukkala, V.; Aloia, T. A.
Abstract : Background: Enhanced recovery (ER) protocols are used widely in surgical practice. As protocols are multidisciplinary with multiple components, it is difficult to compare and contrast reports. The present study examined compliance and transferability to clinical practice among ER publications related to colorectal surgery. Methods: PubMed, Embase and Cochrane Central Register databases were searched for current colorectal ER manuscripts. Each publication was assessed for the number of ER elements, whether the element was explained sufficiently so that it could be transferred to clinical practice, and compliance with the ER element. Results: Some 50 publications met the reporting criteria for inclusion. A total of 22 ER elements were described. The median number of elements included in each publication was 9, and the median number of included patients was 130. The elements most commonly included in ER pathways were early postoperative diet advancement (49, 98 per cent) and early mobilization (47, 94 per cent). Early diet advancement was sufficiently explained in 43 (86 per cent) of the 50 publications, but only 22 (45 per cent) of 49 listing the variable reported compliance. The explanation for early mobilization was satisfactory in 41 (82 per cent) of the 50 publications, although only 14 (30 per cent) of 47 listing the variable reported compliance. Other ER elements had similar rates of explanation and compliance. The most frequently analysed outcome measures were morbidity (49, 98 per cent), length of stay (47, 94 per cent) and mortality (45, 90 per cent). Conclusion: The current standard of reporting is frequently incomplete. To transfer knowledge and facilitate implementation of pathways that demonstrate improvements in perioperative care and recovery, a consistent structured reporting platform is needed. Abstract : Sound recommendations to standardize reporting